Transfusion of blood products and clinical outcomes for patients with dengue fever: a systematic review and meta-analysis - Goh, Zhi Jie (2024)
Background: This systematic review and meta-analysis aimed to analyze the effects of transfusing “nonpacked red blood cell” blood products in patients with dengue and evaluate the effectiveness in reducing mean hospital stay, bleeding, mortality rate, and intensive care unit requirements. Methods: Four databases were searched for relevant articles. Inclusion criteria were prospective or retrospective randomized or nonrandomized studies investigating the effects of transfusion of blood products in patients with dengue. Results: Nine studies were included in the final meta-analysis. Transfusion of blood products was associated with significantly higher mortality rate (9 studies; odds ratio [OR], 3.59 [95% confidence interval [CI], 1.07–15.98]; I2 = 0%; P = .04) and significantly longer mean hospital stay (6 studies; 0.56 day [95% CI, .03–1.08 day]; I2 = 95%; P = .04). There was no significant difference in the incidence of clinical bleeding (7 studies; OR, 1.13 [95% CI, .77–1.65]; I2 = 39%; P = .54) or intensive care unit requirement (3 studies; OR, 1.59 [.40–6.39]; I2 = 0%; P = .51). Conclusions: Transfusing blood products for patients with dengue showed no benefit and may even be harmful.